2018
DOI: 10.1016/j.jval.2018.04.454
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Biosimilar Insulins Compared to Their Reference Products: A Systematic Review

Abstract: ImportanceFor nearly a century, no generic form of insulin has been available in the United States. However, the first biosimilar insulin, Basaglar, was approved by the U.S. Food and Drug Administration in 2015, and subsequently Admelog and Lusduna in 2017.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 30 publications
(56 reference statements)
0
5
0
Order By: Relevance
“…Firstly, there's a sparse evidence base: relatively few studies compare biosimilar insulins with the originator. 6 A meta-analysis of 11 studies compared biosimilars to insulin glargine and insulin lispro. Six studies found that pharmacokinetic, pharmacodynamic parameters or both were comparable between the biosimilar and originator.…”
Section: Mutually Reinforcing Barriersmentioning
confidence: 99%
See 2 more Smart Citations
“…Firstly, there's a sparse evidence base: relatively few studies compare biosimilar insulins with the originator. 6 A meta-analysis of 11 studies compared biosimilars to insulin glargine and insulin lispro. Six studies found that pharmacokinetic, pharmacodynamic parameters or both were comparable between the biosimilar and originator.…”
Section: Mutually Reinforcing Barriersmentioning
confidence: 99%
“…Adverse events, assessed in all studies, were also comparable. 6 But there is clearly a need for more research.…”
Section: Mutually Reinforcing Barriersmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides, in cases of allergic reactions in individuals, biosimilars provide more alternative options 19 . Owing to the potential benefits of biosimilars, investigation of biosimilars grows around the world, and more biosimilars are trying to join the market 20,30 . Whereas, as the copies of biological medicines have large and complex structures, biosimilars have high order molecular structures and could be affected by various factors, such as modifications in manufacturing, distribution and storage processes, which are associated with protein‐folding/post‐translational changes and eventually could affect efficacy and safety profiles 31,32 .…”
Section: Discussionmentioning
confidence: 99%
“…Even for a specific biosimilar product, the treatment outcomes may vary remarkably through different races. Therefore, it is imperative to conduct comprehensive assessments to evaluate the similarity of biosimilar products to the respective originator product, particularly in efficacy and safety profiles 19,30 . To our knowledge, this is the first study to assess the efficacy and safety of LY IGlar in comparison with IGlar in Chinese patients with T1DM.…”
Section: Discussionmentioning
confidence: 99%